Work Group Climate and Behavioral Responses to Psychological Contract Breach - Shen, Yimo; Schaubroeck, John M.; Zhao, Lei; Wu, Lei (Frontiers in Psychology, 2019)
Drawing on theories of social exchange and social information processing, we examined whether the influence of psychological contract breach on in-role performance and organization-directed citizenship behavior (OCBO) depends on work group climate levels, specifically procedural justice climate and power distance climate. The findings supported our hypothesis that psychological contract breach more strongly influences in-role performance and OCBO among members of units with favorable procedural justice climates. Support for a hypothesized moderating role of power distance climate was less conclusive. We discuss the implications of our model and findings for theories of employee–organization relationships and practice.